Impact of ankylosing spondylitis on sexual function: A systematic review and meta-analysis - LIU, YA-FEI (Exp Ther Med, 2015)
A number of studies have reported the association of sexual problems with ankylosing spondylitis (AS); however, the results have been conflicting. The present study aimed to investigate the impact of AS on sexual function. To develop a more comprehensive understanding of sexual function in patients with AS, a systematic review and meta-analysis of the literature up to 2013 was conducted. Studies that assessed the impact of AS on sexual function by adopting the International Index of Erectile Function or the Female Sexual Function Index (FSFI) scoring system were included. Statistical analysis was performed using Review Manager statistical software (version 5.2). The weighted mean differences were calculated by employing a fixed or random effects model. A total of 484 cases from five studies were identified as being well-documented and included in the meta-analysis. Compared with healthy controls, male patients with AS have a significant reduction in sexual function scores of erectile function (−3.07), orgasmic function (−1.17), sexual drive (−0.72) and intercourse satisfaction (−1.89). Female patients with AS have a lower FSFI score in domains of desire (−0.34) and arousal (−0.87). In conclusion, AS has a certain impact on the sexual function of male patients. AS appears to have a greater influence on the sexual function of males compared with that of females. However, the mechanism by which AS affects sexual function requires further evaluation by further studies of a larger population of patients.